A Rare Case of Nipple–Areolar Complex Partial Necrosis following Micropigmentation: What to Learn?. Issue 11 (November 2019) - Starnoni, Marta; Pinelli, Massimo; Franceschini, Gianluca; De Santis, Giorgio
Abstract : Summary: A 52-year-old woman, without any comorbidity, presented at our institution for reconstruction of nipple–areolar complex (NAC). Nipple reconstruction was obtained through local skin flaps. After 2 months, a tattoo of the NAC was performed. Follow-up was planned at 6 months. Nevertheless, the patient came to our attention 2 days after tattooing for partial necrosis of the epidermal–dermal layer of the tattooed area with partial muscular layer exposition. Empirical antibiotic treatment was immediately started to avoid infection. Daily medications were performed for 3 weeks. Complete healing was obtained within 3 weeks without the necessity of a skin graft. We think that the partial necrosis of the NAC occured because of vascular impairment of the dermal and subdermal vascular plexus during micropigmentation. From this experience, we developed some advice to improve our clinical practice by allowing surgeons, especially if trainees, to avoid complications in performing NAC micropigmentation.